2009
DOI: 10.1002/glia.20863
|View full text |Cite
|
Sign up to set email alerts
|

Stat3 inhibition activates tumor macrophages and abrogates glioma growth in mice

Abstract: As the main effector-cell population of the central nervous system, microglia (MG) are considered to play an important immunoregulatory function in a number of pathological conditions such as inflammation, trauma, degenerative disease, and brain tumors. Recent studies, however, have suggested that the anti-neoplastic function of MG may be suppressed in malignant brain tumors. Considering the proposed suppressive role of signal transducers and activators of transcription 3 (Stat3) in antitumor immunity, we eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
139
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 174 publications
(142 citation statements)
references
References 57 publications
2
139
0
1
Order By: Relevance
“…5C); this was concentrated in the larger tumors. p-Stat3 is a marker of M2 protumor polarized macrophages (28,33). To determine whether macrophages in our tumors might be M2 polarized, we performed immunofluorescence for Iba1 and p-Stat3 and quantified the number of cells that were Iba1 + and p-Stat3 + .…”
Section: Heterozygous Loss Of Ptprd Results In P-stat3 Accumulation Andmentioning
confidence: 99%
See 1 more Smart Citation
“…5C); this was concentrated in the larger tumors. p-Stat3 is a marker of M2 protumor polarized macrophages (28,33). To determine whether macrophages in our tumors might be M2 polarized, we performed immunofluorescence for Iba1 and p-Stat3 and quantified the number of cells that were Iba1 + and p-Stat3 + .…”
Section: Heterozygous Loss Of Ptprd Results In P-stat3 Accumulation Andmentioning
confidence: 99%
“…In addition, recent work by Pyonteck et al showed that RCAS PDGFB gliomas have tumor-associated macrophages, and that inhibiting their polarization state can significantly improve survival (30). Several studies demonstrate that p-Stat3 within macrophages polarizes them to a M2 tumorpromoting state (28,33). We show that Ptprd +/− p16 −/− tumors had higher levels of p-Stat3 in macrophages, demonstrating that Ptprd loss can affect p-Stat3 accumulation in the macrophages and may alter the macrophage state.…”
Section: Discussionmentioning
confidence: 99%
“…В клетках опухолевого микроокружения активность STAT3 значительно повышена, что проявляется гиперэкс-прессией IL-6, IL-10 и снижением экспрессии IL-1 [53]. Блокирование функции STAT3 на мышиных моделях глиом приводило к активации микроглии и торможению опухо-левого роста, что сопровождалось снижением экспрессии IL-10 и СD163 (маркеров иммуносупрессивного М2-фе-нотипа [54]) и других мишеней STAT3 (c-myc, циклин D1, сурвивин, HIF-1 , VEGF).…”
Section: блокирование молекулярных мишеней иммуносупрессии и туморогеunclassified
“…In vitro studies on human monocyte-derived macrophages showed that this compound prevented M2 macrophage polarization, as measured by inhibition of CD163 expression and IL-10 secretion (M2 markers); it also augmented glioblastoma cell apoptosis (Fujiwara et al, 2010). In mouse models, a STAT3 inhibitor or small interfering RNA blocked "immunosuppressive polarization"(principally IL-10 and IL-6 secretion) of microglia stimulated by glioma cell supernatant (Zhang et al, 2009). Furthermore, in orthotopic GL261 murine glioma in vivo, intratumoural STAT3 siRNA injection augmented TNF mRNA expression, and prolonged survival (Zhang et al, 2009).…”
Section: Stat3 Inhibitionmentioning
confidence: 99%
“…In mouse models, a STAT3 inhibitor or small interfering RNA blocked "immunosuppressive polarization"(principally IL-10 and IL-6 secretion) of microglia stimulated by glioma cell supernatant (Zhang et al, 2009). Furthermore, in orthotopic GL261 murine glioma in vivo, intratumoural STAT3 siRNA injection augmented TNF mRNA expression, and prolonged survival (Zhang et al, 2009). …”
Section: Stat3 Inhibitionmentioning
confidence: 99%